A new generation of highly flexible and soft tools for high precision surface finishing with embedded micro-diamonds. (February 2019) - Dvorak, M; Mielemeier, F; Adams, H
Abstract: Fully automated and process-integrated, high-quality surface polishing is still an extremely challenging task. In particular, the final polishing of complex surfaces without affecting the part geometry often remains a problem. A newly developed technology allows the direct embedding of diamonds into the surfaces of polymer and elastomer polishing tissues and sponges without the use of any adhesives. The same technology can be applied for making micro-diamond enhanced brushes with very fine and highly flexible filaments for polishing surfaces of complex geometries as well as customized polishing tools for direct integration in processing machines. This article highlights some of the possibilities as well as limitations of a new generation of flexible, diamond-coated polishing tools.